Effect of Nutrition and Growth Regulators on Growth of Oat - AL- Zubadie, Raam Shakir Mahmood; AL-Naqeeb, Mufaq Abdul Razza (Journal of Kerbala for Agricultural Sciences, 2018)
Afield experiment was condected at the experimential farm of field crop Dept. college of Agriculture university of Baghdad Abu-Ghraib to study the effect of NPK and gibberellen( foliar application) on growth and seed yield of Oat during 2013-2014 season . R.C.B.D design was used with four replications., and two factors ,first was NPK application in four levels NPK1(K 200+P1000+N2500) Mg L-1 ,NPK2(K 300+P1500+N3500) Mg L-1 , NPK3(K 400+P2000+N4500) Mg L-1 and the control(water spraying) .The second was application of gibberellen in four levels0, 200,300,400 Mg L-1 were applied when the plant heights were 50 cm average. The second facter application of gibberellen in four levels 200, 300,400 Mg L-1 and the control o were applied when the plant heights were 50 cm average. The results showed that : NPK3 gave the highest plant height 135.69cm and branches numbers 503.62 branch m-2 and numbers of spike 472.70 spike m-2. NPK3 gave the highest green forage 26.56 Mg ha-1 while the grain yield application of NPK2 gave higher grain yields of oat 4.61 Mg ha-1 . The higher grain yield oat 4.44 Mg ha-1 in application of GA2.There were significant interaction between NPK and gibberellen The interaction between NPK3 and GA3 gave highest studied triats while the interaction between NPK2 and GA3 gave the highest grian yield (5.69) Mg ha-1. Key word:Oat,NPK,GA3,numbers of spike,green forage.